Study of relaxor behavior in a lead-free (Na0.5Bi0.5)TiO3-SrTiO3-BaTiO3 ternary solid solution system. Issue 11 (15th August 2016) - Praharaj, S.; Rout, D.; Subramanian, V.; Kang, S.-J.L.
Abstract: In this work, single phase lead-free (0.8- x )(Na0.5 Bi0.5 )TiO3 −0.2SrTiO3 - x BaTiO3 (NBT-ST-BT) ceramics were prepared by conventional solid state reaction method. The effect of BT on the structure and on the dielectric and ferroelectric properties of NBT-ST-BT were investigated. A structural transformation from pseudo-cubic to tetragonal along with possible phase coexistence was witnessed as the BT content was increased. A diffuse phase transition with considerable frequency dispersion in the dielectric response and slim P-E loops evidenced strong relaxor behavior for the ternary system at higher compositions of BT. An analysis of the frequency dependent Tm according to V-F and Power law indicated substantial interaction between the polar nano-regions and relatively broad distribution of freezing temperatures. The study of the dielectric constant at much higher and lower temperatures than Tm in the range of Burn's temperature (TB ) to freezing temperature (Tf ) to provide useful information about the growth rate of polar nano-regions and their interactions for a better understanding of the relaxor behavior exhibited by the present ternary system.